POTENSI KOMBINASI NANOPARTIKEL FULLERENOL DAN INHIBITOR UREASE DALAM TATALAKSANA FARMAKOLOGIS INFEKSI HELICOBACTER PYLORI: SEBUAH KAJIAN LITERATUR - Nathaniel Gilbert Dyson; Aldithya Fakhri (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Over 50% of global population have been infected by Helicobacter pylori. However, current pharmacological management of Helicobacter pylori infection still possess many challenges, especially antibiotic resistance and side effects of PPI drugs usage. Recent studies have found that fullerenol nanoparticles and urease inhibitors are potential to eradicate Helicobacter pylori infection. Methods: Literature search is done from three international databases, namely PubMed, Scopus, and Google Scholar, independently with previously stated inclusion and exclusion criteria. The final search results in 5 eligible studies which will further be discussed. Discussion: Fullerenol nanoparticles can undergo a pinacol rearrangement and have carboxyl or carbonyl functional group that can act similarly like peroxidase enzyme activity to destroy polysaccharides in the cell wall of Helicobacter pylori. Biotoxicity of the fullerenol nanoparticles in the toxicity test with the Drosophila melanogaster showed no significant side effects. On the other hand, urease inhibitors such as catechol and p-benzonequinol, can decrease ammonia synthesis and lower the pH in the gastric lumen. This condition inhibit growth of Helicobacter pylori and increase the work of fullerenol nanoparticles. Biotoxicity of urease inhibitors are also very low, proved by the morphological changes of human glioblastoma cells (GL-15) in vitro at concentrations above 200 M. Conclusion: Fullerenol nanoparticles act similarly like proxidase enzyme to destroy the cell wall of Helicobacter pylori. On the other hand, urease inhibitors decrease ammonia synthesis and lower gastric lumen pH to prevent infection. Combination of fullerenol nanoparticles and urease enzyme inhibitors are highly potential as pharmacological treatment of Helicobacter pylori.